THE EFFECTS OF ACID MINE DRAINAGE UPON VEGETATION IN THE BOZANTA TAILINGS POND (MARAMUREŞ COUNTY) - JELEA, Oana-Corina (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
Owing to the procedures of processing non-ferrous ores, from Baia Mare mining district, containing Au, Ag, Cu, Pb and Zn, resulted large amounts of flotation tailings, which were deposited in Bozânta tailings pond (located between the villages Săsar and Bozânta Mare, 4 km west of Baia Mare town). Due to the presence of minerals containing metal sulphides (mainly pyrite), the acid rock drainage (ARD) has become very active, catalyzed by iron- and sulphur-oxidizing bacteria, especially those of the genus Acidithiobacillus ferrooxidans, Leptospirillum ferrooxidans, Acidithiobacillus thiooxidans, Thiomonas intermedia and Starkeya novella, which naturally occur in these sites. Bacterial oxidation of these minerals leads to the production of acid rock drainage, contaminating the environment with heavy metals. In this study we investigated the effects of ARD on the tailings, but also on plantations of acacia (Robinia pseudoacacia) from sector 5 (were the tailings was not covered with soil) compared to sectors 1-4 (where the tailings were covered with soil). On the surface of the tailings pond, in sector 5, a non-homogeneous appearance of the flotation tailings can be noticed, with different oxidation stages; landslides; ravines up to 100 cm deep; driftings of tailings and seepage solutions areas. Dependent on the age of the tailings, and the action time of the ARD phenomena, the pH value decreased from 7.7 to 2.9. The decrease in pH below 5 caused the vegetation to die. When additional countermeasures of covering with soil the tailings were taken in the sectors 1-4 of the tailings pond, the effects of the ARD phenomena were diminished and helped vegetation flourish.